Correlation between mandibular third molar and mandibular incisor crowding: A retrospective CBCT-based study - Seerab Husain; Sri Rengalakshmi (Tabriz University of Medical Sciences, 2021)
Background. Late mandibular incisor crowding is a fairly common phenomenon experienced by growing adults. The etiology of late mandibular incisor crowding, however, is controversial and inconclusive. Hence, this study aimed to investigate the correlation between mandibular third molar and mandibular incisor crowding using Cone-beam computed tomography (CBCT) data. Methods. The study consisted of 40 samples of CBCT images divided into two groups (n=20). Group A comprised CBCT images without third molars, and group B included CBCT images with third molars. The images were observed in the axial view and manually marked to calculate the amount of crowding using Little's irregularity index. The obtained values were statistically analyzed using Pearson's correlation test. SPSS 23 was used for statistical analysis. Results. The results showed a positive correlation between the mandibular third molars and mandibular incisor crowding, which was significant (P=0.033). The mean Little's irregularity index score for groups A and B were 4.26 and 6.799, respectively (P=0.033). Conclusion. The positive correlation between the two groups suggests an association between the mandibular third molars and mandibular incisor crowding.